Antibacterial effect of an herbal product persica on porphyromonas gingivalis and aggregatibacter actinomycetemcomitans: an in-vitro study. - Zahra Jelvehgaran Esfahani; Zeinab Kadkhoda; Seyed Saeed Eshraghi; Mohammad Hossein Salehi Surmaghi (Tehran University of Medical Sciences, 2014)
The plant Salvadora persica is used for oral hygiene in many parts of the world. It has been suggested that it has antibacterial properties, in addition to its ability to mechanically remove plaques. The aim of this study was to assess the antimicrobial activity of the herbal product Persica containing Salvadora persica against periodontopathogens Porphyromonas gingivalis and Aggregatibacter actinomycetemcomitans in vitro.Fifty patients with moderate and severe periodontitis were recruited. Using paper points, subgingival plaque samples were taken from pockets with attachment loss ≥ 3mm. The samples were subjected to microbial culture to yield P. gingivalis and A. actinomycetemcomitans. The ditch plate method was used for antimicrobial susceptibility testing of the bacteria to Persica compared to chlorhexidine and distilled water. The growth inhibition zones of microorganisms around the ditches were measured in millimeters. The data were analyzed using SPSS 16. Freidman test and Wilcoxon signed ranks test with Bonferroni adjustment were used for analysis of variance with 5% significance level. P